40 років інституту етнографічних досліджень Угорської академіїї наук - Мушкетик, Л. (Народна творчість та етнографія, 2007)
The article is dedicated to a 40-year anniversary of Institute of Ethnographic Research of Hungarian Academy of Sciences headed by famous scientist Migal Goppal. The author presents structure and history of this Institute, main lines of investigations, main editions, text and monograph publications, interacademic relations with Maksym Rylsky Institute of Art Criticism, Folklore and Ethnography.